(3CKhdhLjG CQSWGWGdjSs - (3JaSjQ aQahQjhS GdUhQis
(3ChdgG (B:s
(3ef cJGH GQSWhWGdjS GdajdSha GdeSei HGdjhfGfjI CKhdhLjG s
(3BNQgG (B:s
(3heG ajg ef GdCTjGA GdMSjI hcd eG ai gPG GdYGde gh ai Pdc GdYGde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs